The Influence of Training, Customer Orientation and Work Engagement on The Hotel Supervisor Professionalism - Dewi Eka Arini; Dedi Purwana; Muchlis R. Luddin (IJHCM (International Journal of Human Capital Management), 2020)
The hospitality industry has grown in size and complexity to service demands that require a higher level of skills from its personnel. Qualified personnel and skilled personnel are at the core of any profession, thus the professional status of the hotel industry should encourage to maintain the quality of employees. This study aims to determine the effect of training, customer orientation and job engagement on the professionalism of hotel supervisors in the hotel industry in Indonesia based on the rapidly changing needs of customers in the industry. The data collected was taken from a national hotel chain totaling 49 hotels from several regions in Indonesia and taking a sampling of 219 supervisors.